Effect of high-pressure processing on texture and color of crossbreed F1 Senepol/Nelore cattle beef - Otavio Cabral Neto; Rosires Deliza; Sabrina Luzia Grégio de Sousa; Tatiana Saldanha; Ormindo Domingues Gamallo; Wellington Barros dos Santos; Amauri Rosenthal (Scientia Agricola)
ABSTRACT This research study endeavored to examine the impact of high-pressure processing (HPP) on the texture and color of post-rigor mortis beef, explicitly focusing on the Longissimus dorsi muscle obtained from the crossbred F1 Senepol/Nelore breed of cattle. Pressure levels ranging from 100 to 400 MPa were exerted at varying processing times on beef sourced from animals of both genders (males and females). Subsequently, the samples were assessed for tenderness, cooking loss, and color. HPP at 100 and 200 MPa promoted significant increases (p < 0.05) in tenderness regardless of sex, based on decreases in shear force in instrumental texture analyses. A significant increase in cooking loss was detected at higher pressures (more than 300 MPa). HPP made a statistically significant impact (p < 0.05) on specific color parameters, and overall, the treatment at 200 MPa resulted in more positive effects.